A PHILOSOPHICAL EXAMINATON OF KARATE’S PLAUSIBILITY IN MORAL EDUCATION - KAUKA, ELVIS OMONDI (IJRDO- Journal of Educational Research, 2018)
This Philosophical Study sought to examine whether Karate as a sport can be reasonably  justified as a means towards moral development of students and the public at large. The study infers that indeed Karate is not just a sport but most importantly a do (an ethical life style). Karate Practitioners (Karatekas) use their techniques (the Te ) in the training hall, in tournaments and when in extreme danger, but for most of their ordinary lives they use the do. Methods used include Philosophical analysis, Descriptive method and In-depth interview. The Study first outlines Karate history, then exposes the necessity of moral education in learning institutions. An explication of Karate’s ethical ramifications, an analysis of the exquisite and explicit moral nexus Karate and the report of an In-depth interview with one of the Sensei’s in Kenya a presented successively. The conclusion affirms that Karate is relevant in Moral education.